Molecular phylogeny of the genus Myosotis (Boraginacea) based on nrDNA ITS sequences - Mahboubeh Sherafati; Shahrokh Kazempour Osaloo; Maryam Khoshsokhan Mozaffar; Shokouh Esmaeilbagi; Nasim Saadati (تاکسونومی و بیوسیستماتیک, 2014)
Myosotis, forget-me-not, is one of the genera of Boraginaceae-Boraginoideae. This genus consists of about 100 species distributed predominantly in the temperate zones of both hemispheres. Myosotis has two centers of diversity-one in western Eurasia and the other in New Zealand. In Iran, 15 species of this genus has been identified. Myosotis species are small tiny perennial and annual plants characterized by smooth nutlets. In this study, 58 accessions (including 56 taxa as ingroups and two taxa Echiochilon persicum and E. fruticosum as outgroups) were included for the phylogenetic analyses using nrDNA ITS sequence data. Phylogenetic analyses were performed using maximum parsimony approach as implemented in PAUP* software, Bayesian inference using Mr Bayes program and Maximum Likelihood method using raxmlGUI program. The heuristic search of the MP analysis resulted in 10000 shortest trees of 786 steps length with a consistency index (CI) = 0.482 and a retention index (RI) = 0.770 (excluding uninformative characters). In the trees resulting from maximum parsimony, Bayesian and maximum likelihood methods, Myosotis was monophyletic and composed of six distinct monophyletic clades (A-F). In contrast to the sectional classification system (sections Myosotis and Exarrhena), the subgeneric classification system (subgenera Myosotis and Strophiostoma) for the genus are supported. Annual species did not form a monophyletic group, instead, they were dispersed among biennials and perennials across the tree. Likewise, the species growing in Iran and southwest Asia were scattered across the tree among other species of the genus.